(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence and characteristics of yeast species isolated from clinical samples at 103 Military Hospital from January 2023 to March 2025. Subjects and methods: A retrospective cross-sectional descriptive study was conducted from January 1, 2023, to March 30, 2025, involing 511 patients who were indicated for fungal culture at 103 Military Hospital. Diagnostic techniques included culture on Sabouraud medium and identification of Candida species on CHROMagar™ Candida. Results: Among 511 patients, 199 cases were positive, yielding a positivity rate of 38.9%. The age group ≥ 56 years had the highest positivity rate (42.8%) with a statistically significant difference (p = 0.02). Yeast dominated with 158 isolates, in which the Candida genus accounted for the highest proportion (95.5%). The most common yeast species included: C. albicans (45.5%), C. tropicalis (30.3%), and C. krusei (20.1%). Notably, the study recorded 1.2% of Talaromyces marneffei isolates from corneal scrapings in non-immunocompromised patients. The majority of fungal isolates were obtained from respiratory specimens (77%). Conclusion: Accurate identification of the causative fungal species is essential to guide treatment and manage antifungal activity more effectively.